Economic Analysis of Cross Breeding Programs for Indigenous Goat Breeds in Uganda - Onzima, R.; Aheisibwe, A. R.; Katali, B. K.; Arendonk, J. A. M. van (WCGALP, 2014)
This study evaluates the economic viability and profitability of crossbreeding programs for improving indigenous goat breeds under smallholder subsistence production systems in Uganda. A survey was conducted among 156 households in 4 districts of South Western Highlands Agro-Ecological zone where cross-breeding programs have been implemented to assess the economic potential of improved and indigenous goats. Farm input and outputs in improved and indigenous goat production systems, coupled with information from secondary literature was utilized in an economic analysis to compare the two genotypes. Gross margin analysis revealed that cross breeding is overall beneficial, but under the smallholder subsistence system, the economic benefits are not significant. It is therefore concluded that to realize the full genetic potential of the crossbreds, the genetic improvement of the indigenous breeds needs to be accompanied by improved management